Policy-relevant systematic reviews to strengthen health systems: models and mechanisms to support their production. (25th May 2016) - Oliver, Sandra; Dickson, Kelly
Abstract : Support for producing systematic reviews about health systems is less well developed than for those about clinical practice. From interviewing policy makers and systematic reviewers we identified institutional mechanisms which bring systematic reviews and policy priorities closer by harnessing organisational and individual motivations, emphasising engagement between policy and research, embedding efforts in conducive structures and supporting them with formalised procedures. Four models combine mechanisms appropriately to suit the initial degree of clarity and consensus of key issues underpinning the policy problem or research question, and whether the review is for a specific decision or widespread use.